Linkage Mapping Identifies the Sex Determining Region as a Single Locus in the Pennate Diatom Seminavis robusta - Vanstechelman, Ives (Public Library of Science, 2013)

(untitled)
The pennate diatom Seminavis robusta, characterized by an archetypical diatom life cycle including a heterothallic mating system, is emerging as a model system for studying the molecular regulation of the diatom cell and life cycle. One of its main advantages compared with other diatom model systems is that sexual crosses can be made routinely, offering unprecedented possibilities for forward genetics. To date, nothing is known about the genetic basis of sex determination in diatoms. Here, we report on the construction of mating type-specific linkage maps for S. robusta, and use them to identify a single locus sex determination system in this diatom. We identified 13 mating type plus and 15 mating type minus linkage groups obtained from the analysis of 463 AFLP markers segregating in a full-sib family, covering 963.7 and 972.2 cM, respectively. Five linkage group pairs could be identified as putative homologues. The mating type phenotype mapped as a monogenic trait, disclosing the mating type plus as the heterogametic sex. This study provides the first evidence for a genetic sex determining mechanism in a diatom.